Nanomaterials for Agricultural and Ecological Defense Applications: Active Agents and Sensors. (21st March 2021) - Sharma, Pramila; Kumar, Sanjay; Patel, Axita; Datta, Bhaskar; DeLong, Robert K.
Abstract: The world we live in today is overpopulated with an unprecedented number of people competing for fewer and fewer precious resources. The struggle to efficiently steward and manage these resources is a global problem in need of concrete and urgent solutions. Nanomaterials have driven innovation in diverse industrial sectors including military, aviation, electronic, and medical among others. Nanoscale materials possess unique surfaces and exquisite opto‐electronic properties that make them uniquely suited to environmental, biological, and ecological defense applications. A tremendous upsurge of research activity in these areas is evident from the exponential increase in publications worldwide. Here we review recent applications of nanomaterials toward soil health and management, abiotic and biotic stress management, plant defense, delivery of the RNA Interference (RNAi), plant growth, manufacture of agro‐products, and ecological investigations related to farming. For example, nanomaterial constructs have been used to counter environmental stresses and in plant defense and disease diagnosis. Nanosensor chemistries have been developed to monitor water quality and measure specific pollutant levels. Specific nanomaterials such as silver, iron oxide, and zinc oxide proffer protection to plants from pathogens. This review describes progress in nanomaterial‐based agricultural and ecological defense and seeks to identify factors that would enable their wider commercialization and deployment. This article is categorized under: Diagnostic Tools > Biosensing Toxicology and Regulatory Issues in Nanomedicine > Toxicology of Nanomaterials Diagnostic Tools > Diagnostic Nanodevices Abstract : Applications of nanomaterials.